THE INFLUENCE OF MOTHER'S KNOWLEDGE AND ATTITUDE ON BASIC IMMUNIZATION COVERAGE - Herlina, Nina; erik ekowati; Dhea firanti, Alfida Faqih; Hildatrian, Elsya; Prudencia, Fairy; Wanelis, Wanelis; Ramadhani, Nabilla (UNIVERSITAS AIRLANGGA, 2024)
Background: Basic Immunization is the administration of vaccines to infants aged 0-18 months. The success of the basic immunization program in infants is supported by the important role of parents who are responsible for their babies Objective: To determine the influence of mothers' knowledge and attitudes on basic immunization coverage. Methods: The research design used was correlational analysis with a cross sectional approach. The sampling technique used is total sampling. The population and sample of all babies aged 12-59 months at the Mande Health Center in September 2023 amounted to 58 people. The instruments used are questionnaires and leaflets. Analyze data with Chi Square. Results: 58 mothers who had babies were obtained in 14 babies with incomplete immunization status, there were 3 (21.4%) mothers who had less knowledge and 11 (78.6%) mothers who had good knowledge. Meanwhile, in 44 mothers with complete immunization status, 42 (95.5%) mothers have a confident attitude towards immunization, while 2 (4.5%) mothers have an unsure attitude towards immunization. Conclusion: There is an influence of maternal knowledge and attitudes with basic immunization status in Jamali Village.